Assessing Vitamin D Levels in Fortified Foods and Supplements for Infants and Its Impact: A Review - Durgadevi A.; Hariram S. (International Journal of Nutritions, 2024)
In this study, the vitamin D levels in fortified foods (including follow-on formula, baby porridge, and curd cheese dessert) and dietary supplements designed for infants were examined. Analytical assessments uncovered variations in vitamin D concentrations compared to the labeled values, fortified foods contain anywhere from 50% to 153% for supplements 8% to 177%. Instant follow-on formula and oil-based supplements typically aligned with or surpassed the labeled values, whereas ready-to-eat baby porridge consistently registered below the declared values (74–81%). The study suggests that relying solely on label information may lead to inaccurate estimations of vitamin D intake in infants, with potential for both underestimation and overestimation. Furthermore, the discrepancies observed in nutrition D concentrations spotlight the importance of regular monitoring and quality manage measures within the manufacturing and distribution of fortified meals and dietary dietary supplements for babies. Adequate nutrition D intake is critical for most effective bone health and immune function throughout infancy, making accurate estimation essential for preserving typical fitness and well-being. The findings underscore the need for greater transparency and accuracy in labeling practices in the infant nutrition industry. Additionally, healthcare experts must be vigilant in advising caregivers about capability variations in vitamin D content material and the significance of varied assets to ensure babies receive adequate vitamins for healthy increase and development. Further studies is warranted to discover the elements contributing to these discrepancies and to establish standardized tips for nutrition D fortification in little one foods and supplements.
Keywords: Dietary supplements; Fortified Foods; HPLC; Vitamin D; infants